Neogene paleoelevation of intermontane basins in a narrow, compressional mountain range, southern Central Andes of Argentina - Hoke, Gregory D. (2014)
The topographic growth of mountain ranges at convergent margins results from the complex interaction between the motion of lithospheric plates, crustal shortening, rock uplift and exhumation. Constraints on the timing and magnitude of elevation change gleaned from isotopic archives preserved in sedimentary sequences provide insight into how these processes interact over different timescales to create topography and potentially decipher the impact of topography on atmospheric circulation and superposed exhumation. This study uses stable isotope data from pedogenic carbonates collected from seven different stratigraphic sections spanning different tectonic and topographic positions in the range today, to examine the middle to late Miocene history of elevation change in the central Andes thrust belt, which is located immediately to the south of the Altiplano-Puna Plateau, the world’s second largest orogenic plateau. Paleoelevations are calculated using previously published local isotope-elevation gradients observed in modern rainfall and carbonate-formation temperatures determined from clumped isotope studies in modern soils. Calculated Neogene basin paleoelevations are between 1 km and 1.9 km for basins that today are located between 1500 and 3400 m elevation. Considering the modern elevation and δ18O values of precipitation at the sampling sites, three of the intermontane basins experienced surface uplift between the end of deposition during the late Miocene and present. The timing of elevation change cannot be linked to any documented episodes of large-magnitude crustal shortening. Paradoxically, the maximum inferred surface uplift in the core of the range is greatest where the crust is thinnest. The spatial pattern of surface uplift is best explained by eastward migration of a crustal root via ductile deformation in the lower crust and is not related to flat-slab subduction.